Konsep Perancangan Interior âMotocross Centreâ di Surabaya - Andereas Pandu Setiawan, Laurentius Elson T.L (Intra, 2013)
Motocross in Indonesia has been known since many years ago especially in big citis. But the available facilities in Surabaya do not support. That is why a motocross centre is neeeded as a place for hobbiers, to fullfil their needs in Surabaya. The other problem for the motocrossers is the uncertain weather at the outdoor track. The weather is a primary aspect to be put into acount whenever they want to carry out their hobby. Their for, this indoor motocross centre is design for them to do it without being interfered by the weather and they do not have to go down the outdoor track or down the traffic road.